2014
DOI: 10.1103/physrevlett.112.233003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Splitting of the 2s1/2 and 2p1/2 Levels

Abstract: High-resolution spectroscopy of the 2s(1/2)-2p(1/2) transition in the extreme ultraviolet region is shown to resolve the level splitting induced by the nuclear magnetic field of both the 2s(1/2) and the 2p(1/2) levels in lithiumlike (141)Pr(56+) and of the 2s(1/2)2p(1/2) (3)P(1) level in berylliumlike (141)Pr(55+). The (141)Pr ions are an ideal test of this measurement approach because their energy levels are known well from first principles and are unaffected by small energy contributions from QED and nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…As already mentioned, an important boost to the field of optical spectroscopy with HCI occurred as both ion storage rings (Klaft et al, 1994;Seelig et al, 1998) and EBITs (Beiersdorfer et al, 2001;Crespo López-Urrutia et al, 1996 reported HFS measurements in hydrogenlike ions of heavy elements. It was clear that scaling laws would shift the 21 cm microwave transition of atomic hydrogen into the optical region, and reduce its enormous 11 million years lifetime to milliseconds.…”
Section: Measurements Of the Hfs Of Hydrogenic Ionsmentioning
confidence: 97%
See 3 more Smart Citations
“…As already mentioned, an important boost to the field of optical spectroscopy with HCI occurred as both ion storage rings (Klaft et al, 1994;Seelig et al, 1998) and EBITs (Beiersdorfer et al, 2001;Crespo López-Urrutia et al, 1996 reported HFS measurements in hydrogenlike ions of heavy elements. It was clear that scaling laws would shift the 21 cm microwave transition of atomic hydrogen into the optical region, and reduce its enormous 11 million years lifetime to milliseconds.…”
Section: Measurements Of the Hfs Of Hydrogenic Ionsmentioning
confidence: 97%
“…The first direct observation of a hyperfine splitting (HFS) in the optical range was achieved by resonant laser excitation of the M1 transition coupling the two hyperfine levels of the ground state of hydrogenlike 209 Bi 82+ ions circulating at relativistic velocities in the GSI heavy-ion storage ring ESR (Klaft et al, 1994), followed by spontaneous-emission measurements of 187 Ho 66+ (holmium, Z = 67) ), 185,187 Re 74+ (rhenium, Z = 75) ((Crespo López-Urrutia et al, 1998a)), and 203,205 Tl 80+ (thallium, Z = 81) (Beiersdorfer et al (2001)) ions trapped in an EBIT, and a further experiment on 207 Pb 81+ (Seelig et al, 1998) at ESR. In all those experiments, systematic effects, low resolution and statistics limited the relative wavelength accuracies to about 1 × 10 −4 .…”
Section: Fine and Hyperfine Structure Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The team at GSI has tried to induce this transition for many years, and only recently a resonance has been seen, the frequency of which still needs to be located with accuracy in the rest frame of the speedy ion [49,50]. Concurrently the Livermore SuperEBIT has provided EUV/soft-x-ray spectra of 2s-2p 3/2 and 2s-2p 1/2 line multiplets in Bi and Pr from which the hyperfine splitting of the 2s 1/2 and the 2p 1/2 electrons could be determined [51][52][53]. The hyperfine intervals make up only a fraction of the EUV transition energy, and, consequently, the accuracy of the determination of the hyperfine interval is lower than what ultimately the direct laser resonance experiment should be able to achieve.…”
Section: Active Interrogationmentioning
confidence: 99%